2001
DOI: 10.1021/jp0043064
|View full text |Cite
|
Sign up to set email alerts
|

Branching Ratio and Pressure Dependent Rate Constants of Multichannel Unimolecular Decomposition of Gas-Phase α-HMX:  An Ab Initio Dynamics Study

Abstract: The dynamics of the initial thermal decomposition step of gas-phase α-HMX is investigated using the master equation method. Both the NO2 fission and HONO elimination channels were considered. The structures, energies, and Hessian information along the minimum energy paths (MEP) of these two channels were calculated at the B3LYP/cc-pVDZ level of theory. Thermal rate constants at the high-pressure limit were calculated using the canonical variational transition state theory (CVT), microcanonical variational tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…In addition, the quantum tunneling effects were included in the rate constant calculations with the SCT tunneling method [38][39][40] employed to calculate the transmission coefficient in the CVT framework, and Eckart tunneling model 29,41,42 employed in the VT framework. There are considerable literatures on the TST, CVT, and VT formalisms.…”
Section: Rate Constant Calculationsmentioning
confidence: 99%
“…In addition, the quantum tunneling effects were included in the rate constant calculations with the SCT tunneling method [38][39][40] employed to calculate the transmission coefficient in the CVT framework, and Eckart tunneling model 29,41,42 employed in the VT framework. There are considerable literatures on the TST, CVT, and VT formalisms.…”
Section: Rate Constant Calculationsmentioning
confidence: 99%
“…The earlier calculation results have shown that the N-NO 2 bond rupture is putatively one of the most important initial reactions for the thermal decomposition of nitramine [19,[26][27][28]. Here, we first considered the N-NO 2 bond dissociation reactions for the HMX and the three complexes (PHMX1, PHMX2 and AHMX) as shown in Scheme 1.…”
Section: N-no 2 Bond Dissociationmentioning
confidence: 99%
“…Several theoretical studies have also been reported on the energetics of gas-phase decomposition pathways for HE materials using a variety of methods. For example, we point to work in RDX and HMX where both quantum chemistry [44][45][46][47] and classical simulations of unimolecular dissociation 48,49 were used.…”
Section: Atomistic Modeling Of Condensed-phase Reactionsmentioning
confidence: 99%